Implementation of Class Visits Supervision to Determine Teacher Professionalism - Elok Sundus; Istikomah Istikomah; Nyong ETIS; Isa Anshori (International Consortium of Education and Culture Research Studies, 2020)
The presence of supervision at a school is an indispensable activity. One such supervision technique is a class visit. The purpose of this research is to find out how the implementation of supervision in the School with class visit techniques and their impact on the level of professionalism of teachers. This research uses a qualitative approach to the study of phenomology in SMP At-Tibyan. The main data sources are the Principal and Teacher. This study also uses a sampling procedure with research subjects of 5 teachers with different tenure at the school. The data collection technique is observation and is supported by interview techniques as a source of supporting data. Data analysis techniques according to Miles and Huberman include condensation of data, presentation of data, drawing conclusions. The results obtained are 1) the implementation of supervision of classroom visits has increased in terms of technical implementation, 2) the level of professionalism of At-Tibyan Middle School teachers is still low, 60% includes Professional teachers, 20% includes quite professional teachers, and 20% of teachers are not professional. The development of teacher professionalism needs to be done immediately and the role of the school principal can effectively support the development of the teacher's professionalism. As a controlling stage for the business, academic supervision can be carried out with classroom visits techniques that continue to improve the quality of implementation. Through supervision of class visits can be seen developments in the level of professionalism of teachers.